Research design process formalization - Палагін, Олександр Васильович; Опанасенко, Володимир Миколайович (Problems of Informatization and Management, 2019)
The analysis of the main development paths of the fourth industrial revolution (Industrie 4.0), which is designed to carry out enhanced integration of cyberphysical systems (CPS) into production processes and the Internet of things (IoT), is carried out. Industrie 4.0 - is the production side, equivalent to the consumer-oriented IoT, in which household items, from cars to toasters, will be connected to the Internet and will be able to receive feedback from the final product, assembly, machine, household appliance. All this must happen with the introduction of intelligent robots. The main industries that will be transformed using IoT are presented. All this contributes to the development of the Digital Economy. The international organization OECD (Organization for Economic Co-operation and Development) identifies one of the main components of the digital economy "Supporting infrastructure (hardware and software, telecommunications, networks, etc.)". The era of intensive development of smart systems of various levels and purposes is supported by the Horizon 2020 strategic framework program and the joint technological initiative (JTI) Electronic Components and Systems for European Leadership (ECSEL) for the period up to 2024. and the joint venture of the same name ECSEL JU. The multi-year strategic plan for the implementation of the research and innovation program in the field of electronic components, systems and technologies (MARSIA) provides the development of the following main domains: smart mobility, smart society, smart energy, smart health and smart production. The analysis of Internet of Things technology - Smart systems, cyber-physical systems, their applications and construction features based on FPGA chips is performed.A formalized method is proposed for the research design of structural implementations for an arbitrary problem in an arbitrary subject area by choosing the optimal (method - architecture) pair, consisting in solving the structure synthesis problem based on constructs of an alphabet for performing a specific algorithm A that implements the method that realization the structure functioning, in accordance with the requirements of the specifications. The result of the procedure is the description of the project in the CAD input language.